Dutch girl : [compact disc, unabridged] Audrey Hepburn and World War II - Matzen, Robert, 1957- (Blackstone Publishing, 2019)
Biographers have chronicled Audrey Hepburn's stardom, but none has covered her experiences through five years of Nazi occupation in the Netherlands, including participation in the Dutch Resistance, assisting doctors during the battle of Arnhem, and undergoing the Hunger Winter of 1944. She had to contend with her father being a Nazi agent, and became Arnhem's most famous young ballerina.